Neoliberalism and neoliberals: What are we talking about?. Issue 1 (22nd August 2019) - Lipscomb, Martin
Abstract: The terms neoliberalism and neoliberal play a variety of roles ranging from major to trivial in the papers they appear in. Both phrases carry pejorative connotations in nurse writing. Yet irrespective of the role assumed in argument, readers are rarely provided with enough information to determine what the descriptors mean in a substantive or concrete sense. It is proposed that scholars who use these terms in their work should consider expressing themselves more carefully than often occurs at present. Virtue signalling in academic writing should, absent critical argument, be discouraged.